Учет неосесимметричности течения в осевых турбомашинах - Коваль, В. А.; Ковалева, Е. А.; Романов, В. В.; Скворцов, А. В. (НТУ "ХПИ", 2008)
The approach under the account of the defective phenomena is observed by development of mathematical models of current in meridional plane of axial turbomachines. Comparison of designs and skilled radial distributions of axial and peripheral making speeds behind the vane wheel rotor of a step of the axial-flow compressor is resulted.
Keywords: электрические машины; поля течений; числа Маха; кривизна линий тока; симметрия потока; решетки турбинных профилей; предсрывной режим; коэффициент аэродинамического загромождения